Social Welfare Provision at Local Level: A Case Study on Istanbul Metropolitan Municipality - Arikan, Elif Sinem (Argumentum, 2016)
In this article I tried to find traces of a neo-conservative model the Istanbul Metropolitan Municipality in Turkey. Firstly I tried to explain significant collaboration between liberalism and conservatism in the neoliberal context. Subsequently, I tried to evaluate the Istanbul Metropolitan Municipality to see the neoconservative administration’s effects on local administrations based on market-oriented administration rationale. I tried to explain that the gender discourse was strengthened because of such administration rationale. I tried to evaluate this matter profoundly. I mentioned the Ladies Commission of RP (Welfare Party) and Kadın Koordinasyon Merkezi (Women Coordination Center (WCC)) in the Istanbul Metropolitan Municipality as examples of models of conservative women’s political organizations.